Multiple vertical axis wind turbines with passive rectification to a common DC-link. (November 2018) - Rossander, Morgan; Fjellstedt, Christoffer; Bernhoff, Hans
Abstract: Wind turbines are commonly placed in wind farms, usually operating as separate units. Possible benefits could be found by allowing turbines to share a common DC-link. Diode rectifiers are a robust and cost effective way to rectify variable speed wind turbines, with loss of direct control of the generator. This paper studies the electromechanical interactions between four passively rectified vertical axis wind turbines connected to a common DC-link. Two different load approaches for the DC-link are compared using simulations in terms of performance and stability: a power source and a voltage source. The optimal torque (or optimal power) control is implemented for the two loads approaches. In addition, three-phase and dual stator winding (six-phase) generators are compared. The results show that all suggested solutions work with similar performance. However, the power load requires a large DC-link capacitance to achieve stability. More generatorphases improve the system with passive rectiﬁcation in most cases. The simulations suggest that the common DC-link systems are expected to have a few percent lower energy capture due to the lack of individual turbine control. On the other hand, there is a significant reduction in peak power and a potential for smoother output power. Graphical abstract: Image 1 Highlights: A wind turbine farm with diode rectified PMSGs to a common DC-link could be a low complexity and highly reliable system. This paper studies electromechanical interaction and stability of such a system using theoretical analysis and simulations. The stability with different two different load strategies is presented. Three-phase and dual three phase winding generators are also compared.